2011
DOI: 10.1111/j.1365-2850.2011.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

Societal participation: examining the impact of a rehabilitation approach for young people with schizophrenia

Abstract: This paper is based on research that focuses on the impact of a rehabilitation approach with respect to 99 young people diagnosed with schizophrenia in a Dutch mental health facility. The approach focused on societal participation goals. Nurses and social workers play a key role in such treatment. The research focused on developmental trajectories and showed significant improvement with respect to societal participation levels. Impairment scores remained stable. The results indicate that rehabilitation counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The main question in this study was to find care factors that can be influenced by MHC workers in order to achieve SR and/or FR. The predictive value found for the change in unmet care needs in psychological distress and daytime activities for FR and psychological distress and company for SR is in line with several studies (Meesters et al 2013;Ochoa et al 2003;Van Wel and Landsheer 2012;Wiersma et al 2009). Other studies (Chang et al 2013) have also found that social-environmental factors have an important influence on recovery.…”
Section: Discussionsupporting
confidence: 87%
“…The main question in this study was to find care factors that can be influenced by MHC workers in order to achieve SR and/or FR. The predictive value found for the change in unmet care needs in psychological distress and daytime activities for FR and psychological distress and company for SR is in line with several studies (Meesters et al 2013;Ochoa et al 2003;Van Wel and Landsheer 2012;Wiersma et al 2009). Other studies (Chang et al 2013) have also found that social-environmental factors have an important influence on recovery.…”
Section: Discussionsupporting
confidence: 87%
“…These approaches are based on principles of respect and a partnership with people receiving healthcare (Hamann et al, 2006; Law, Baptiste, & Mills, 1995). One problem regarding implementation of the BPR is that traditional mental healthcare systems often have a main focus on the reduction of psychotic symptoms and the prevention of relapses (Van Wel & Landsheer, 2011). A strict provider-centered approach in mental health services mainly focusing on medical treatment may not automatically increase quality of life and the ability to achieve personal goals among persons with severe mental illness (Chee, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional mental healthcare system in Sweden, like in many other counties, has a strong normative orientation, with a main focus on the reduction of psychiatric symptoms and the prevention of relapses (Van Wel & Landsheer, 2011). This indicates an adherence to behavioral norms mandated for successfully obtaining and maintaining needed support such as housing or entry into a community reintegration program (Lovell, Richmond, & Shern, 1993; Shern et al, 2000).…”
mentioning
confidence: 99%
“…The mental health-care system in Sweden, as in many other counties, has a strong focus on the reduction of psychiatric symptoms and prevention of relapses (Van Wel & Landsheer, 2011 ) in which positive dimensions of health have not been viewed as suitable for evidence-based practice in health care (Jormfeldt, 2011 ). Barriers regarding health promotion among persons with severe mental illness have been associated with stigma, as well as professional and organizational obstacles in the health-care services provided (Ehrlich et al, 2014 ).…”
mentioning
confidence: 99%